The Private Financing of Higher Education - Hahn, Ryan (International Higher Education, 2008)
In recent years, cost sharing has been on the rise. The growth of mechanisms such as bond issuances, private equity, and philanthropy have marked an increased role for private finance in higher education, but these mechanisms have not been widely adopted. Both students and institutions continue to face credit constraints on worthwhile educational investments. While private finance presents its own risk, if greater cost sharing is to achieve what its proponents claim it cannamely, greater efficiency, equity, and accessprivate finance will have to play a greater role in overcoming these credit constraints.